Pengaruh Kualitas Produk, Iklan, dan Promosi terhadap Brand Awareness pada Prudential Life Assurance - Sembiring, Fauji Arkhan; Daulay, Aqwa Naser; Jannah, Nurul (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study examines the effects of product quality, advertising, and promotion on brand awareness in the life-insurance context. Using a quantitative survey of 100 respondents and multiple linear regression, the research tested the partial and simultaneous influences of the three predictors. Instrument quality met common thresholds for validity and reliability; classical assumptions were assessed prior to model estimation. The results show that product quality does not have a significant partial effect on brand awareness (p = 0.138), whereas advertising (p = 0.003) and promotion (p = 0.021) have positive and significant effects. Simultaneously, the model is significant (F = 35.726; p < 0.001) with an explanatory power of R² = 0.684. These findings indicate that communication efforts—particularly consistent and creative advertising and targeted promotions—play a more decisive role in strengthening brand awareness than perceived product quality in this sample. The study provides managerial guidance for prioritizing integrated marketing communication strategies for life-insurance brands